2001
DOI: 10.1590/s0074-02762001000900029
|View full text |Cite
|
Sign up to set email alerts
|

Infection by Schistosoma mansoni sambon 1907 in the first four months of life of Biomphalaria straminea (Dunker, 1848) in Brazil

Abstract: Compatibility between Schistosoma mansoni and Biomphalaria straminea when exposed to the parasite on the first four months of age was assessed for five parasitological aspects: indices of infection and mortality, duration of precercarial and cercarial periods, and rate of cercarial emission. Infections were made on molluscs from laboratory colonies, at the following ages: 8, 13, 18, 21, 53, 83 and 114 days. Two B. straminea colonies were used (Camorim, PE and Picos, PI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…However, the exposed positive snails (n = 13) presented an 86.6% survival rate. This difference has been attributed either to the parasite strain or to the susceptibility profile, age and size of the mollusc population, in addition to the time elapsed since exposure (Sorensen and Minchella, 2001;Fernandez and Pieri, 2001). These results might be associated with the finding that the development of the larvae is slower in infected snails that do not release cercariae, leading to gradual consumption of the energy reserves.…”
Section: Resultsmentioning
confidence: 99%
“…However, the exposed positive snails (n = 13) presented an 86.6% survival rate. This difference has been attributed either to the parasite strain or to the susceptibility profile, age and size of the mollusc population, in addition to the time elapsed since exposure (Sorensen and Minchella, 2001;Fernandez and Pieri, 2001). These results might be associated with the finding that the development of the larvae is slower in infected snails that do not release cercariae, leading to gradual consumption of the energy reserves.…”
Section: Resultsmentioning
confidence: 99%
“…In the north-east of Brazil, the prevalence of S. mansoni infection in B. straminea ranges from 11 to 24% [38, 39], while artificial exposures of S. mansoni to B. straminea in the laboratory have shown low infectivity, with prevalence ranging from 1.2 to 1.6% depending on the strain of miracidia being tested [40]. Close to the border between Hong Kong and mainland China, in the city of Shenzhen, a recent study reported that the black-coloured B. straminea collected in the field were resistant to S. mansoni infection [41].…”
Section: Discussionmentioning
confidence: 99%
“…The snails were individually exposed to 5 Schistosoma mansoni miracidia from Camorim, State of Pernambuco (CM strain), Picos, Piauí (EC strain) and Padre Bernardo, Goiás (PB strain). The CM and EC strains were isolated as described by Fernandez and Pieri (2001). The PB strain was isolated on June 30, 1998 from feces of VP Silva, 21 years, born and grown up in Amorim, Padre Bernardo, GO, an urban focus of schistosomiasis since 1997 (Amaral & Alves 1997), ranging approximately 300 km from the lake of the UHSM.…”
mentioning
confidence: 99%
“…However, infection indices up 10% were obtained by some investigators: Paraense (1967) obtained 3 positive snails of 28 specimens from Fordlândia, Pará (index of 10.7%); Souza et al (1983) found 11 out of 100 specimens from Jequitibá, Minas Gerais (11%); and Fernandez and Pieri (2001) found 217 positive snails among 1,691 specimens from Camorim, Pernambuco (12.8%). The lengthening of the precercarial period is also in accordance with that described by Favre et al (1995) and Fernandez and Pieri (2001) for this species.…”
mentioning
confidence: 99%